Sleep Disturbances in Children With Autism Spectrum Disorder at a Malaysian Tertiary Hospital - Koo, Ho Wai; Ismail, Juriza; Yang, Wai Wai; Syed Zakaria, Syed Zulkifli (Frontiers in Pediatrics, 2021)
INTRODUCTION: Children with autism spectrum disorder (ASD) have a variety of co-morbid medical problems; including sleep disturbances. Prevalence of sleep disorders has been reported to be higher in this group as compared to the general population. Identifying sleep problems in children with ASD may help increase awareness and improve the overall quality of care for them. The aim of this study was to determine the prevalence of sleep problems and associated factors in a group of Malaysian children aged 6 to 16 years, with ASD. METHOD: This is a cross-sectional study at the Child Development Centre of UKM Medical Centre (UKMMC) on ASD children aged 6–16 years. Demographic data was obtained and the Sleep Disturbances Scale for Children (SDSC) questionnaire was completed by the main caregiver. Logistic regression analysis was used to determine factors related to higher total SDSC scores. RESULTS: A total of 128 patients were recruited (111 boys) with a median age of 8 years 3 month (IQR: 2 years 10 months). Forty-seven (36.7%) of them obtained total SDSC scores in the pathological range with 19 (14.8%) scoring high for overall disturbances and 28 (21.9%) for at least one subtype of sleep disorders: 25 (19.5%) DIMS, 18 (14.1%) SBD, 10 (7.8%) DOES, 5 (3.9%) DOA, 6 (4.7%) SWTD, and 3 (2.3%) SHY. More than half of the children (57.8%) were reported to have sufficient sleep duration of 8-11 hours, but longer sleep latency of at least 15 minutes (82.8%). Half of the ASD children also had co-morbidities in which one-third (34.4%) had attention-deficit hyperactivity disorder (ADHD). Using logistic regression analysis, four factors were significantly associated with higher total SDSC scores; female gender (p = 0.016), older age group (11-16 years old) (p = 0.039), shorter sleep length (p = 0.043) and longer sleep latency (p < 0.001). CONCLUSION: The prevalence of sleep disturbances is high among Malaysian children with ASD, especially DIMS. Female gender, older age group, shorter sleep length and longer sleep latency were found to be associated with the sleep disturbances. Evaluation of sleep problems should form part of the comprehensive care of children with ASD.